Class Difference Depicted in the Work of E.M. Forster - Syrová, Alžběta (Univerzita Pardubice, 2019)
This bachelor thesis deals with the portrayal of class difference in the so-called Italian novels by E. M. Forster. The thesis describes the differences between an upper and middle-class at the beginning of 20th century and how the difference complicated relationships. Moreover, the thesis deals with cultural distinctions stemming from the difference between traditional British society and Italian progressivism.
Třídní rozdíly v díle E.M. Forstera
Keywords: class difference; social values; tradition; Room with a View; Where Angels Fear to Tread; Forster, E. M.; Victorian era; třídní rozdíly; společenské hodnoty; tradice; Pokoj s vyhlídkou; Kam se bojí vkročit andělé; Forster, E. M.; Viktoriánská doba